Not Just Where, But How Does a Seizure Start?. Issue 4 (July 2019) - Gotman, Jean
The Repertoire of Seizure Onset Patterns in Human Focal Epilepsies: Determinants and Prognostic Values Lagarde S, Buzori S, Trebuchon A, Carron R, Scavarda D, Milh M, McGonigal A, Bartolomei F. Epilepsia. 2019;60(1):85-95. doi: 10.1111/epi.14604. PMID: 30426477 Objective: In this study, we seek to analyze the determinants of the intracranial electroencephalography seizure onset pattern (SOP) and the impact of the SOP in predicting postsurgical seizure outcome. Methods: To this end, we analyzed 820 seizures from 252 consecutive patients explored by stereoelectroencephalography (total of 2148 electrodes), including various forms of focal refractory epilepsies. We used a reproducible method combining visual and time-frequency analyses. Results: We described 8 SOPs: low-voltage fast activity (LVFA), preictal spiking followed by LVFA, burst of polyspikes followed by LVFA, slow wave/DC shift followed by LVFA, sharp theta/alpha waves, beta sharp waves, rhythmic spikes/spike-waves, and delta-brush. Low-voltage fast activity occurred in 79% of patients. The SOP was significantly associated with (1) underlying etiology (burst of polyspikes followed by LVFA with the presence of a focal cortical dysplasia, LVFA with malformation of cortical development, postvascular and undetermined epilepsies), (2) spatial organization of the epileptogenic zone (EZ; burst of polyspikes followed by LVFA with focal organization, slow wave/DC shift followed by LVFA with network organization), and (3) postsurgical seizure outcome (better outcome when LVFA present). Significance: This study demonstrates that the main determinants of the SOP are the underlying etiology and the spatial organization of the EZ. Concerning the postsurgical seizure outcome, the main determinant factor is the spatial organization of the EZ, but the SOP plays also a role, conferring better prognosis when LVFA is present.